Pengaruh Media Pembelajaran Roda Putar terhadap Pemahaman Konsep Belajar - Rendy Nugraha Frasandy (Universitas Islam Negeri Imam Bonjol Padang, 2025)
The study aimed to examine the effect of using Roda Putar as a learning medium to improve pupils’ conceptual understanding at elementary madrasah teacher education studenst. The research applied a quantitative approach with a quasi-experimental method, using a pretest–posttest control group design. The samples were selected through cluster random sampling, with class I-E as the experimental group and class IF as the control group. Data were collected through observation, tests, and documentation, and were analysed using the t-test with SPSS version 26. The results show that the experimental class achieved an average post-test score of 85.88, while the control class scored 77.06. The average N-gain scores were 81.65 and 63.61 respectively. The significance value of 0.000 (p 0.05) indicates a meaningful difference. It can be concluded that the ROTAR learning media effectively enhances pupils’ conceptual understanding